2017
DOI: 10.1371/journal.pone.0174273
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of small G protein RhoB in the regulation of proliferation, adhesion and migration by dexamethasone in osteoblastic cells

Abstract: Long-term exposure to therapeutic doses of glucocorticoids (GCs) results in bone remodeling, which frequently causes osteoporosis and fracture healing retardation because of the abnormality of osteoblastic proliferation and differentiation. The mechanisms of GCs’ effect on osteoblasts are largely unknown. In this present study, we found that dexamethasone (Dex) could induce the expression of the small G protein, RhoB, in mRNA and protein levels in the osteoblast-derived osteosarcoma cell lines MG-63. The up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…We also showed that RhoB was downregulated in osteosarcoma tissues and low expression of RhoB predicted poor prognosis of osteosarcoma patients. Furthermore, in lung cancer and osteoblastic cell RhoB mediated cell proliferation, adhesion, migration and invasion in lung cancer and osteoblastic cell 27,28. In our study, knockdown of miR-19a inhibited osteosarcoma cell EMT through RhoB.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We also showed that RhoB was downregulated in osteosarcoma tissues and low expression of RhoB predicted poor prognosis of osteosarcoma patients. Furthermore, in lung cancer and osteoblastic cell RhoB mediated cell proliferation, adhesion, migration and invasion in lung cancer and osteoblastic cell 27,28. In our study, knockdown of miR-19a inhibited osteosarcoma cell EMT through RhoB.…”
Section: Discussionsupporting
confidence: 58%
“…RhoB, usually acted as a tumor suppressor, which was associated with multiple cellular progresses, including cell growth, adhesion and transformation 2325. In lung cancer, RhoB regulated the activity of PP2A to modulate mesenchymal phenotype and invasion 26,27. Diao et al28 discovered that RhoB mediated cell proliferation, adhesion and migration in osteoblastic cells.…”
Section: Introductionmentioning
confidence: 99%